Protective efficacy of a lipid antigen vaccine in a guinea pig model of tuberculosis. Issue 10 (7th March 2017) - Larrouy-Maumus, Gérald; Layre, Emilie; Clark, Simon; Prandi, Jacques; Rayner, Emma; Lepore, Marco; de Libero, Gennaro; Williams, Ann; Puzo, Germain; Gilleron, Martine
Highlights: M. tuberculosis antigenic lipids in liposomes were evaluated as subunit vaccines. The lipid vaccine induced a significant reduction of bacteria in the spleen. The lipid vaccine lowered the disease pathology in both lungs and spleen. Vaccination with lipid antigens can induce some protection in the guinea pig model. Abstract: The bacillus Calmette Guérin (BCG) vaccine, the only licensed vaccine against TB, displays partial and variable efficacy, thus making the exploitation of novel vaccination strategies a major priority. Most of the current vaccines in pre-clinical or clinical development are based on the induction of T cells recognizing protein antigens. However, a large number of T cells specific for mycobacterial lipids are induced during infection, suggesting that lipid-based vaccines might represent an important component of novel sub-unit vaccines. Here, we investigated whether immunization with defined mycobacterial lipid antigens induces protection in guinea pigs challenged with M. tuberculosis . Two purified mycobacterial lipid antigens, the diacylated sulfoglycolipids (Ac2 SGL) and the phosphatidyl- myo- inositol dimannosides (PIM2 ) were formulated in biophysically characterized liposomes made of dimethyl-dioctadecyl-ammonium (DDA) and synthetic trehalose 6, 6′-dibehenate (TDB). In three protection trials, a reduction of bacterial load in the spleen of inoculated animals was consistently observed compared to the unvaccinated group. Moreover, a reduction in the number of lesions and severity of pathology was detected in the lungs and spleen of the lipid vaccine group compared to unvaccinated controls. As the degree of protection achieved is similar to that observed using protein antigens in the same guinea pig model, these promising results pave the way to future investigations of lipid antigens as subunit vaccines.